An fMRI study on auto-determined and etero-determined finger movements - Bertollo, M.; Comani, S.; Caulo, M.; Tartaro, A. (International Journal of Computer Science in Sport, 2002)
The relationship between perception and action can be considered a starting point for a study on motor control and learning. Direct and indirect theories can be studied from a phenomenological or structural perspective. Among the ecological theories the dynamic system approach believes that movement patterns arise from complex interactions among the various motor elements, and consequently hypothesizes that new movement learning might occur through a self-organization process. Aim of this study was to verify by means of fMRI what cortical areas are activated and what learning processes are triggered during the execution of voluntary movements under different boundary conditions. Ten volunteers (6 males, age between 22 and 26 years, estimated to be neurologically normal) participated to the study after informed consent. A Siemens Vision Whole Body Scanner, 1.5 T permanent magnet, was used for MR imaging. The experimental protocol consisted of a blocked-trial paradigm in which five rest phases alternated with four task phases, consisting in the execution of a bimanual anti-phase flexion-extension of the index fingers. During the first and the second task phases volunteers could choose the execution velocity, which had to be maintained slow during the first and rapid during the second task phase. On the other hand, during the third and fourth task phases execution velocities were pre-set at 1.5 Hz and 3.4 Hz respectively for the slow and the rapid movements. Functional scans were acquired with Echo Planar Imaging (EPI) sequences and processed with SPM96 and MEDx software packages. Different patterns of activation were observed for control and learning processes during auto-and etero-determined movement execution. The most important results obtained for the comparison between the rapid and the slow movements executed in free modality were the activation of the frontal and inferior pre-frontal cortex, associated to planning processes. Moreover the activation of the cingulate gyrus, the parietal lobes, the basal ganglia, the thalamus and the cerebellum was observed, probably in relation to a movement reorganization following a phase-transition. The activation of these structures devoted suggests that an implicit learning may occur when the execution velocity increases to the point that a phase transition takes place. On the other hand, maps obtained for the comparison between the rapid and the slow movements executed under acoustic guidance show no significant activation, probably because the execution velocity was not too high even during the forth task phase, and no phase transition took place.